A model for predicting two-phase flow patterns transitions in annulus: inclinations from horizontal to near-vertical - Oliveira, Marciellyo Ribeiro de (2021)
The flow of a two-phase mixture is a complex phenomenon. One reason is that interactions between phases depend on variations in operating conditions (velocity of the phases, pressure, tube geometry, etc). These operating conditions impose the formation of different flow patterns that can undergo pattern transition depending on the change in geometric cross-section. This work proposes a mechanistic model for any tube inclination from horizontal to near-vertical and considers the concentric annulus condition as a particular case of a pipe. Mathematical relationships are developed to calculate shear stresses and velocity profiles in an annulus under different inclinations. Based on geometric parameters, a new methodology helps obtain the wetted area and perimeter of the liquid and gas phase. Furthermore, two scenarios are considered to verify the model’s reliability: horizontal piping and vertical piping, and good performance was found in both scenarios. Finally, a generalized air-water flow pattern map based on dimensionless groups is obtained. Furthermore, the influence of the inner tube on the stratified liquid level is studied, and it is found that the insertion of the inner tube causes an increase in the liquid level as the superficial gas velocity increases. Also, the influence of the tube inclination in the following transitions between flow patterns is verified: smooth stratified/wavy stratified, wavy stratified/annular dispersed liquid, stratified/intermittent, annular dispersed/intermittent, and intermittent/dispersed bubble. Regardless of the direction, the intermittent flow pattern is the most affected, increasing its area as the inclination increases if the flow is upward and decreasing its area as the inclination increases if the flow is downward.